Strategi Menanamkan Kesantunan Berbahasa Melalui Penguatan Profil Pelajar Pancasila dalam Pembelajaran PAI dan Budi Pekerti - Ananda Munifatul Olifiya; Ratnasari Diah Utami (Elementary Teacher Education Program, Majalengka University, 2024)
Education is an important determinant of the progress of a country and nation. Character education has a very important role to maintain a balance between technological progress and human growth in this era of rapid technological progress. Therefore, this study seeks to describe how the teacher's strategy in instilling language politeness through strengthening the Pancasila Student Profile in PAI and Budi Pekerti learning. This research uses qualitative and descriptive methodology. The data collection approaches used include interviews, observation, and documentation. To assess the accuracy of the data, researchers used source triangulation and technique triangulation. The data obtained in this study went through three stages of data analysis: data reduction, data presentation, and conclusion drawing. The results obtained by this study have shown that the strategy of instilling language politeness in class IV students in PAI and Budi Pekerti lessons at SD Negeri 3 Nogosari is carried out using the following methods, namely: 1) Providing habituation activities to students by practicing saying